Book Review: Leading from the Top: Directors Who Make the Difference. (March 2015) - Poomath, Jaidev
N. Balasubramanian, Leading from the Top: Directors Who Make the Difference . IIM Ahmedabad Book Series/Random House India. 2013, 304 pp., ₹ 299. ISBN 978-8-184-00316-1